Marketing process adaptation: Antecedent factors and new product performance implications in export markets. Issue 3 (6th May 2014) - A. Griffith, David; S. Lee, Hannah; Seob Yeo, Chang; Calantone, Roger
Abstract : Purpose: – The purpose of this paper is to explore the marketing "processes" of governing multiple export relationships under the theoretical framework of governance value analysis (GVA). Specifically, this work examines the internal exchange attributes of transaction-specific investments and psychic distance on the adaptation/standardization of relational behavior and detailed contracting and how process adaptation/standardization influences new product outcomes and jointly created value in the focal export relationship. Design/methodology/approach: – A survey was conducted of 151 US manufacturers regarding their relationship with their primary foreign buyers. Data were analyzed with partial least squares estimation. Findings: – The results indicate that high levels of transaction-specific investments lead to the adaptation of relational behaviors whereas high levels of psychic distance lead to less adaptation of detailed contracting. The adaptation of relational behaviors and detailed contracting reflect differential direct effects on export performance. Furthermore, the results indicate that there is a significant positive interaction effect between the adaptation of relational behavior and detailed contracting on jointly created value in the focal export relationship. Practical implications: – The findings of the study reveal that adaptation of the marketing process related to relationship governance strategies can play an important role in the export marketing process, but managers must proceed with caution in balancing relational behavior and detailed contract adaptation. The results also point to the importance of understanding the underlying source of uncertainty and adapting appropriate aspects of governance for enhancing jointly created value in the export relationship. Originality/value: – The value of this research lies in its goal to highlight the issue of marketing process adaptation across multiple export relationships. Less attention has been paid to the marketing "processes" of governing multiple export relationships in the international marketing strategy literature relative to "program" standardization/adaptation. This is one of the first empirical studies on marketing process adaptation of governance employing the theoretical framework of GVA.